Perubahan dan Pengembangan Organisasi Sudut Pandang Manajemen Organisasi - Lukman Hakim; Sujudi, Muhammad (Journal of Law and Administrative Science, 2024)
Organizational Development is a long-term and comprehensive strategy to bring an organization to its highest functional level. Organizational Development focuses on changing employee attitudes, values and beliefs so that they are able to identify and implement technical changes for the betterment of the organization. This research uses qualitative research with the research results that Organizational Development is based on two important assumptions: Humans have a desire to develop and want to contribute to the organization. Organizational Development aims to remove obstacles within the organization that hinder employee development and contribution. Everyone can be accepted and recognized for their role in the group. Organizational Development fosters openness and interaction between group members to increase job satisfaction and group performance. It was concluded that the relationships between groups in an organization determine the effectiveness of each group. Organizational Development encourages interaction between group members to improve coordination and cooperation. Organizational Development is the key to delivering an organization to reach peak performance amidst dynamic change.